Predictors of adherence to clinical breast examination and mammography screening among Malaysian women. - Kandiah, Mirnalini; Parsa , Parisa (Asian Pacific Organization for Cancer Prevention, 2010)
Breast cancer is the most common cancer among Malaysian women and early detection can play an important role in reducing cancer morbidity and mortality. The aim of this cross-sectional study was to determine the rates and factors related to clinical breast examination (CBE) and mammography among 425 female teachers in Selangor, Malaysia. A self-administered questionnaire that included questions on socio-demography, cancer-related knowledge practice and an adapted version of Champion's revised Health Belief Model Scale was employed. The mean age of participants was 37.2±7.16 years. Only 25% of the women ever had a CBE. Of women over the age 40 (n=138), 13.6% reported having had a mammography. The results showed higher susceptibility to breast cancer, higher benefits of doing CBE and regular visits with a physician to be significant predictors for undergoing CBE (p<0.05). In addition, higher a perceived susceptibility to breast cancer and regular undergoing CBE were significant predictors for having a mammography. The findings clearly suggest a need for improving women's awareness on breast cancer screening, its importance and recommended guidelines.